The analytical hierarchy process based study for sustained quality engineering practices - Mohd. Yusof, Sha'Ri (2015)
Organizations regardless of their size and sector need to measure and review their quality performance strategically and tactically for gaining a competitive advantage. The primary purpose of this paper is to empirically identify and analyze the measures perceived as important for assessing business excellence practices within the United Arab Emirates context. Eight factors with a total of 52 practice sub-factors have been identified and derived from an extensive literature review followed by expert’s panel assessment. A self-administered questionnaire survey is conducted to confirm the adaptability of the proposed measured with 138 companies from different sector and business. The Analytic Hierarchy Process (AHP) method was employed to perform the required statistical analysis of the data collected from surveys. Based on analysis, five factors including 29 sub-factors have proposed as excellence practices measures for assessing business excellence practices. The proposed measures then become the main constructs and basis for developing a self-evaluation instrument in the future research. The proposed factors can be used by companies for testing quality performance and self-assessment as well as benchmarking. It shows the existing quality and performance level on strengths and weaknesses, and where improvements need to be made.